THE EFFECT OF DIASPORA ON PUNJABI CULTURE - Singh, Surjit (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Punjabi diaspora, spanning across continents such as North America, Europe, Australia, and the Middle East, has significantly shaped and transformed Punjabi culture. This article explores the multifaceted impact of the diaspora on Punjabi traditions, language, music, cuisine, and identity. It examines how migration has led to the global dissemination of Punjabi culture, the emergence of hybrid identities, and the preservation of traditions, while also addressing challenges such as cultural dilution and generational disconnect. Drawing on historical migration patterns, sociological perspectives, and contemporary examples, this article highlights the dynamic interplay between the diaspora and the homeland in shaping modern Punjabi culture.